Pola Komunikasi Interpersonal Orang dengan Lupus (Odapus) dalam Masyarakat (Studi Fenomenologi Pola Komunikasi Interpersonal Odapus pada Komunitas Griya Kupu Solo dalam Masyarakat) - Ahimsha, Roosvina Lasdafi, Rinasari Kusuma, M.I.Kom, Palupi, M.A (2014)
Communication is an indispensable necessity of every human being. As social being, humans cannot- not communicate with each other. Therefore, communication, particularly interpersonal communication, becomes an essential need for every human being to attain relationship and mental health. The subjects in this study are three people with Lupus (odapus). Selection of the subject based on the consideration that there is no sufficient information in the community about lupus and odapus. The aim of this research is to determine the Odapus's pattern of interpersonal communication. This study uses a qualitative method with a phenomenological approach. Using this approach, researcher is trying to understand the meaning of events and situations experienced by odapus. This study finds that the pattern of interpersonal communication of People with Lupus (odapus) can be improved because of the positive self-concept within odapus. The positive self-concept, such as : The desire to continue the descent, fulfill their necessity as social beings, belief for keeping alive, the confidence to communicate with others, empathy, motivation (support) , imitation and self actualization.